2019
DOI: 10.1111/liv.14154
|View full text |Cite
|
Sign up to set email alerts
|

The concept of therapeutic hierarchy for patients with hepatocellular carcinoma: A multicenter cohort study

Abstract: Alessandro Vitale and Fabio Farinati equally contributed to this work.Prognosis and designing a treatment modality in patients with hepatocellular carcinoma (HCC) are extremely complex because, in most cases, this neoplasm is accompanied by the cirrhotic liver and other comorbidities. 1 Thus in such cases, tumour stage, the degree of liver function and general conditions of patients are the major deterministic factors. 2,3 A common and promising approach linking prognostic variables with therapeutic choice is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 26 publications
6
50
0
Order By: Relevance
“…(5) The peculiarity of patients with HCC (i.e., multiple fundamental prognostic variables besides tumor features and the availability of several evidence-based treatments) has prompted the introduction of another approach, which associates prognostic variables to the treatment decision, thereby creating prognostic systems that simultaneously suggest treatment indications. (1,(6)(7)(8) In 1999, the Barcelona Clinic Liver Cancer (BCLC) group proposed the seminal treatmentdictating staging system for HCC, which associated each stage (or substage) to a specific treatment. (6) The BCLC classification was generated following the analysis of the results of randomized controlled studies which evaluated a particular treatment modality against the placebo between patients with comparable tumor characteristics and liver function.…”
Section: Treatment Of Hepatocellular Carcinoma In the Precision Medicmentioning
confidence: 99%
See 1 more Smart Citation
“…(5) The peculiarity of patients with HCC (i.e., multiple fundamental prognostic variables besides tumor features and the availability of several evidence-based treatments) has prompted the introduction of another approach, which associates prognostic variables to the treatment decision, thereby creating prognostic systems that simultaneously suggest treatment indications. (1,(6)(7)(8) In 1999, the Barcelona Clinic Liver Cancer (BCLC) group proposed the seminal treatmentdictating staging system for HCC, which associated each stage (or substage) to a specific treatment. (6) The BCLC classification was generated following the analysis of the results of randomized controlled studies which evaluated a particular treatment modality against the placebo between patients with comparable tumor characteristics and liver function.…”
Section: Treatment Of Hepatocellular Carcinoma In the Precision Medicmentioning
confidence: 99%
“…(42) A detailed description of the existence of a "therapeutic hierarchy" for HCC has been reported recently by the Italian Liver Cancer group (ITA.LI.CA). (8) Working with a large consecutive cohort of patients with HCC (n = 4,867), the authors identified, on the basis of survival benefit observed in clinical practice, a distinct therapeutic hierarchy irrespective of tumor stage, liver function, patient's general condition, and calendar period. This finding was obtained using a multivariate model adjusted with the inverse probability weight method to control for pretreatment imbalances of the baseline variables, thereby eliminating treatment selection bias arising from the survival analysis.…”
Section: Concept Of Therapeutic Hierarchy Origin and Definitionmentioning
confidence: 99%
“…In large HCC, thermal ablation with radiofrequency is unable to achieve response rates and outcomes comparable to those observed in smaller tumours, 1 and the efficacy of transarterial chemoembolization is debatable 25,26 . Recently, a therapeutic hierarchy (determined by the decreasing survival benefit starting from LT, through progressively less radical treatments, to best supportive care [BSC]) has been demonstrated, irrespective of stage 27 …”
Section: Introductionmentioning
confidence: 99%
“…In assessing cancer patients, every clinician responsible for therapeutic decision making is routinely faced with a fairly chal- In their seminal paper published in this issue of Liver International, Vitale et al take a rather innovative approach by reporting survival outcomes of a large multi-centre patient dataset on the basis of six therapeutic strategies ranging from liver transplantation to best supportive care. 5 As stage classifier, they utilise ITA.LI.CA., a validated prognostic system that takes into account size and number of HCC nodules, vascular invasion, alpha-foetoprotein (AFP) levels, Child-Pugh score and performance status. 6 The rather provocative finding that emerges from this study is the documentation of a clear gradient in overall survival across therapeutic modality independent of stage.…”
Section: Therapeutic Hierarchy In Hepatocellular Carcinoma: a Disputementioning
confidence: 99%
“…In their seminal paper published in this issue of Liver International, Vitale et al take a rather innovative approach by reporting survival outcomes of a large multi‐centre patient dataset on the basis of six therapeutic strategies ranging from liver transplantation to best supportive care . As stage classifier, they utilise ITA.LI.CA., a validated prognostic system that takes into account size and number of HCC nodules, vascular invasion, alpha‐foetoprotein (AFP) levels, Child‐Pugh score and performance status …”
mentioning
confidence: 99%